2021
DOI: 10.1590/fst.03420
|View full text |Cite
|
Sign up to set email alerts
|

Trace analysis of environmental endocrine disrupting contaminant bisphenol A in canned, glass and polyethylene terephthalate plastic carbonated beverages of diverse flavors and origin

Abstract: Bisphenol A (BPA) is a hazardous contaminant demonstrating endocrine disrupting properties, and assumed to be involved in the pathogenesis of various cancer diseases for instance prostate, lung and breast cancer. The objective of the present study was to estimate the BPA amounts in carbonated beverages from the Saudi Arabian market for the first time using an authenticated technique based on solid-phase extraction and ultra-performance liquid chromatography-tandem mass spectrometry. A total of thirty-four carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Studies on polycarbonate bottles showed that increased temperature and repeated use caused an increased release of BPA to water [3], but the concentration in the water was still low enough not to exceed the TDI [49,50]. Additionally, bottles for soft drinks were also tested [51] and the highest concentrations were detected in drinks packaged in glass bottles. These results indicate that contamination with BPA might come from sources other than bottle material, i.e., during food processing or from the environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on polycarbonate bottles showed that increased temperature and repeated use caused an increased release of BPA to water [3], but the concentration in the water was still low enough not to exceed the TDI [49,50]. Additionally, bottles for soft drinks were also tested [51] and the highest concentrations were detected in drinks packaged in glass bottles. These results indicate that contamination with BPA might come from sources other than bottle material, i.e., during food processing or from the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Although our current study, as well as some other studies, show that migration levels of BPA to food simulants are below current SML, the question of the frequency of use of various products, cumulative effect and variety of exposure arises. A number of authors [45,46,48,51,56,57] suggest that humans are almost ubiquitously exposed to BPA and food contamination that might come from different sources, such as contact material during cleaning and contact material during preparation, along with different packaging materials that might have a cumulative effect. Ginter-Krmarzyk et al [52] demonstrated that even though the individual concentrations of BPA in bottled water might be low (ng L −1 ) at 0.6 mg kg −1 per body weight, the cumulative daily dose in the body may be much higher than the quoted concentrations due to the number of products containing BPA.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the consumption of canned foods is widely accepted as one of the primary routes (dietary) of exposure to BPA (Cao et al, 2021; Geens et al, 2012b). For example, Khan et al (2020) determined the occurrence of BPA in carbonated beverage cans from the Saudi Arabian market and found that these may be a significant source of dietary exposure to BPA (measured at 0.64–11.41 µg/l beverage). Glass and PET beverage bottles considered to be BPA‐free packaging materials were also analyzed in the same study and found that BPA concentrations in glass‐bottled beverages were surprisingly high (1.92–29.56 µg/l beverage); higher than in cans and PET bottles (0.37–21.83 µg/l beverage) (Khan et al, 2020).…”
Section: Sources and Pathways: Human Exposure To Bpa Via The Lifecycl...mentioning
confidence: 99%
“…For example, Khan et al (2020) determined the occurrence of BPA in carbonated beverage cans from the Saudi Arabian market and found that these may be a significant source of dietary exposure to BPA (measured at 0.64–11.41 µg/l beverage). Glass and PET beverage bottles considered to be BPA‐free packaging materials were also analyzed in the same study and found that BPA concentrations in glass‐bottled beverages were surprisingly high (1.92–29.56 µg/l beverage); higher than in cans and PET bottles (0.37–21.83 µg/l beverage) (Khan et al, 2020). In addition, González et al (2020) estimated that dietary intake of BPA through the consumption of canned and noncanned foodstuffs was 24.9 and 3.11 µg/day, respectively, demonstrating that epoxy resins used as a coating in canned foodstuffs can contribute substantially to the BPA‐related human exposure.…”
Section: Sources and Pathways: Human Exposure To Bpa Via The Lifecycl...mentioning
confidence: 99%
“…BPA is a synthetic high production volume chemical compound and enlisted as endocrine disrupter (Khan et al, 2020). It belongs to category 1 of Endocrine Disruptive Chemicals (EDC) that is severely toxic to living organisms (Adeyi et al, 2019).…”
mentioning
confidence: 99%